A145 "REAL WORLD" SAFETY AND EFFECTIVENESS OF VEDOLIZUMAB FOR ULCERATIVE COLITIS: RETROSPECTIVE STUDY FROM A TERTIARY CARE CANADIAN CENTRE. (1st March 2018) - Kwapisz, L; Jairath, V; Karthik, V; Beaton, M D; Gregor, J C; Khanna, R; Ponich, T; Sey, M; Yan, B; Chande, N
Abstract: Background: Vedolizumab (VDZ), a humanized monoclonal antibody which targets the α4β7 integrin and prevents homing of lymphocytes to the gut, was approved by Health Canada in 2015 for treatment of moderate to severe ulcerative colitis (UC). Its gut selective mode of action offers potential for a lower risk of systemic infection while achieving similar or greater efficacy compared to conventional treatments. Aims: To assess clinical response and safety of VDZ. Methods: Retrospective cohort study from a tertiary care Canadian centre between May 2015 to August 2016. Adult patients with UC treated with VDZ, with follow-up after initiation of therapy, were eligible. Patients were identified through infusion center listings and data abstracted from electronic medical records, review of clinic records, endoscopy reports and infusion centre reports. Clinical response - defined as normalization of stool frequency and absence of rectal bleeding, as well as physician global assessment, and serious adverse events were assessed. Patients were eligible for safety analysis as long as at least one dose was received. Results: Eighty-eight patients were included, with a median age of 47 years (range 18–85), 58% (51/88) male, 53% (47/88) tumor necrosis factor (TNF)-antagonist exposed with a median follow up of 17 weeks (range 0–61 weeks). The median disease duration was 7 years (range 0–46), 61% (54/88) had a history of disease extension beyond the splenic flexure and 23% (20/88) had a history or prior/active smoking. Patients received a median of 5 VDZ doses (range 1–13) and 47% (41/88) were receiving concomitant treatment with prednisone at the initiation of VDZ. 51% (29/57) of patients achieved clinical response by the end of their induction period (week 6) and 56% (20/36) achieved clinical response at 6 months and 64% (44/69) of patients overall achieved clinical response at some point during the study period. 24 patients underwent endoscopic evaluation after starting VDZ of which 7/24 patients (29%) were reported to have mucosal healing or improved mucosa. No infusion reactions were reported. In 7% (6/88) of patients there were reports of an infection which required antibiotics, of which four had an upper respiratory tract infection and only one patient was admitted for treatment of pneumonia. One patient discontinued VDZ secondary to arthralgia and lethargy after their initial dose. Conclusions: VDZ is a safe and effective treatment for UC in routine clinical practice. In this study, clinical response after induction was achieved in over half of patients by week 6 and close to 2/3 overall achieved clinical remission. Only one patient discontinued treatment due to reports of arthralgia and lethargy after the infusion. Funding Agencies: None